A Piano Training Program to Improve Manual Dexterity and Upper Extremity Function in Chronic Stroke Survivors - Villeneuve, Myriam; Penhune, Virginia; Lamontagne, Anouk (Frontiers in Human Neuroscience, 2014)
Objective: Music-supported therapy was shown to induce improvements in motor skills in stroke survivors. Whether all stroke individuals respond similarly to the intervention and whether gains can be maintained over time remain unknown. We estimated the immediate and retention effects of a piano training program on upper extremity function in persons with chronic stroke. Methods: Thirteen stroke participants engaged in a 3-week piano training comprising of supervised sessions (9 x 60min) and home practice. Fine and gross manual dexterity, movement coordination and functional use of the upper extremity were assessed at baseline, pre-intervention, post-intervention and at a 3-week follow-up. Results: Significant improvements were observed for all outcomes at post-intervention and follow-up, compared to pre-intervention scores. Larger magnitudes of change in manual dexterity and functional use of the upper extremity were associated with higher initial levels of motor recovery. Conclusions: Piano training can result in sustainable improvements in upper extremity function in chronic stroke survivors. Individuals with a higher initial level of motor recovery at baseline appear to benefit the most from this intervention.